Chronic Pelvic Pain: Addressing a Common Debilitating Condition of Women - Rouf, Salma (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(3): 126-127